Analisis Penanganan Kasus Kekerasan Perempuan - Handrianus Vianey Melin Wula; Tri Anggraini; Elpius Kalembang; Fransiskus Atok (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to determine the procedures for handling cases of violence against women by the Women and Children Empowerment Service. This study used a qualitative descriptive method with data collection techniques through observation and documentation. Data analysis techniques used data reduction analysis techniques. The results of the research analysis showed that the handling of cases of violence against women by the DP3A of North Central Timor Regency was carried out by the P2TP2A institution. There are four stages of case handling. First, the reporting or complaint stage from victims/partners. Second, acceptance and recording of identity. Third, the assessment or identification stage of victims. Fourth, the implementation of legal services, or psychology. Fifth, termination activities or termination of services to victims. The conclusion of this study shows that the procedures carried out by the DP3A through the P2TP2A have been running well and regularly, so that victims can get legal and psychological support that helps the process of recovery and justice. Even so, fear due to social stigma and lack of public awareness are still obstacles that need to be overcome with education and improved services. Keywords: Handling, Violence, Women.